1997
DOI: 10.1007/s004240050336
|View full text |Cite
|
Sign up to set email alerts
|

Retention of leucocytes in reperfused, isolated hearts does not cause haemodynamically relevant permanent capillary plugging

Abstract: Effects of microspheres (5 microns or 10 microns diameter) and polymorphonuclear leucocytes (PMN) on coronary resistance were compared in beating, non-working isolated guinea-pig hearts (Langendorff preparation). The hearts were buffer perfused (5 ml/min, constant flow) and particles or cells were infused into the coronary system as a bolus (1 ml, 1 min). Coronary perfusion pressure, coronary flow and formation of epicardial transudate were measured before and after bolus administration. Coronary resistance wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
1

Year Published

1998
1998
2013
2013

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 24 publications
0
11
1
Order By: Relevance
“…PMN of guinea pigs and humans show a quantitatively similar degree of adhesion in our model [12]. Therefore, the latter were used to substantially reduce the total number of animals needed.…”
Section: Methodsmentioning
confidence: 96%
See 2 more Smart Citations
“…PMN of guinea pigs and humans show a quantitatively similar degree of adhesion in our model [12]. Therefore, the latter were used to substantially reduce the total number of animals needed.…”
Section: Methodsmentioning
confidence: 96%
“…Therefore, the latter were used to substantially reduce the total number of animals needed. Preparation, intracoronary application and counting of non-adherent human PMN, as well as calculation of their adhesion rate were carried out as described previously [12]. Under basal conditions intracoronary retention has been shown to be 21.6 ± 2.1% [12].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Reducing the number of PMN should not jeopardize the validity of our results because previous experiments in our model have demonstrated that the percentage of PMN retained in reperfused isolated hearts is independent of the number of PMN applied over the range of 0.6×10 6 -10×10 6 PMN [16]. Perfusion was then continued for 30 min at a constant flow of 300 ml/h to allow stabilization.…”
Section: Experimental Protocolmentioning
confidence: 68%
“…Moreover, coronary perfusion pressure was quantified to exclude occurrence of significant capillary plugging. In recent studies, comparing the effects of microspheres (5 and 10 µm diameter) and PMN on coronary perfusion pressure of isolated and constant-volume perfused (5 ml/min) guinea pig hearts exposed to a 15-min ischemia, we could demonstrate that coronary perfusion pressure is a very sensitive parameter in order to exclude significant capillary plugging [12]. The cell activator thrombin was then administered throughout the whole constant-pressure ischemia/reperfusion phase in a concentration of 0.3 U/ml perfusion buffer.…”
Section: Methodsmentioning
confidence: 99%